Complete Genome Sequence of a Novel Porcine Circovirus Type 3 Strain, CH/GX/1776D/2017, Isolated from Guangxi, China - Lu, Bingxia (Genome Announc, 2018)
Porcine circovirus type 3 (PCV3) was first described in 2016 in U.S. swine herds as a pathogenic agent for pigs. To date, PCV3 has been reported to be widely circulating in the United States, China, South Korea, Brazil, Italy, and Poland. Here, we report the genome sequence of a PCV3 strain (CH/GX/1776D/2017) isolated from Guangxi Province in southern China. The sequence data presented in this study will help us better understand the molecular characteristics and genetic diversity of PCV3 in China.